Molecular Analysis of the Accuracy of Phenotypic Sex Assessment by Anglers in Norwegian Atlantic Salmon Fisheries - Grethe Robertsen; Tim Burton; Ola Ugedal; Eva M. Ulvan; Ola H. Diserud; Øyvind Solem; Merethe Hagen Spets; Sten Karlsson; Peder Fiske (Fisheries Management and Ecology, 2025)
A management regulation applied in some recreational Atlantic salmon ( Salmo salar ) fisheries is a moratorium on harvest of female fish, which can only be effective if recreational anglers can consistently discriminate females from males. We used molecular methods to compare angler‐reported sexes of salmon captured in Norwegian populations with the true sexes of the same individuals. We made this comparison (i) among rivers that were subject to female no‐take policies or not within the same year; and (ii) within rivers before and after a female no‐take regulation was instituted. Sex was misclassified for ca. 25% of salmon that were true females, especially those that were large or captured early in the season. Furthermore, true females were misclassified more often when a female no‐take regulation was in effect. We conclude that a management regulation aimed at protecting female salmon in recreational fisheries may be less effective than expected.

Complex relationships between marine growth and age at maturity in Atlantic salmon - Tim Burton; Geir H. Bolstad; Peder Fiske; Gunnel Østborg; Gitte Løkeberg; Eva B. Thorstad (Reviews in Fish Biology and Fisheries, 2025)
Drastic declines in abundance of Atlantic salmon have been attributed to ecosystem change at sea reducing growth in body size, which in turn could impact survival because mortality at sea may be size-selective. A less scrutinized hypothesis proposes that poor growth conditions at sea may also increase mortality if slow growing individuals need more time at sea to become sexually mature with a longer marine residence period also increasing mortality risk. However, published analyses of the relationship or reaction norm between marine growth and age at maturity in salmon suggest that poor growth is linked with both earlier and later maturation. Hence, understanding why these opposing norms of reaction for age at maturity arise may be critical for elucidating the effects of maturation timing on the dynamics of Atlantic salmon populations. As a step toward this goal, we explain how developmental threshold theory can account for the contrasting norms of reaction that have been observed between marine growth and age at maturity in salmon. To aid our explanation, we construct and interpret a growth in body length at sea vs. age at maturity reaction norm from nearly 4000 individuals returning to the River Namsen in Norway, showing that rapid marine growth can be linked with later maturation and that maturation age can be influenced by shifts in growth occurring during the marine migration. We discuss possibilities for future studies that might yield a better understanding of the relationship between growth at sea and age at maturity in Atlantic salmon.

The influence of mucilage-rich flours from diverse Australian Plantago species on the pasting, storage, and gluten-free breadmaking properties of rice flour - James M. Cowley; Yi Ren; Lucija Štrkalj; Tim J. Foster; Rachel A. Burton (Food Hydrocolloids, 2025)

High Capacity for Physiological Plasticity Occurs at a Slow Rate in Ectotherms - Tim Burton; Sigurd Einum (Ecology Letters, 2025)
Phenotypic plasticity enables organisms to express a phenotype that is optimal in their current environment. The ability of organisms to obtain the optimum phenotype is determined by their (i) capacity for plasticity, which facilitates phenotypic adjustment corresponding to the amplitude of environmental change but also their (ii) rate of plasticity, because this determines if the expressed phenotype lags behind changes in the optimum. How the rate of‐ and capacity for plasticity have co‐evolved will thus be critical for the resilience of organisms under different patterns of environmental change. To evaluate the direction of the evolved relationship between plasticity rate and capacity, we reanalysed experiments documenting the time course of thermal tolerance acclimation to temperature change across species of ectothermic animals. We found that the rate and capacity with which thermal tolerance responds plastically to temperature change are negatively correlated, a pattern inconsistent with current theory regarding the evolution of phenotypic plasticity.

Global Eocene-Oligocene unconformity in clastic sedimentary basins - Zachary F.M. Burton; Tim R. McHargue; Stephan A. Graham (Earth-Science Reviews, 2024)

Global mercury concentrations in biota: their use as a basis for a global biomonitoring framework - David C. Evers; Joshua T. Ackerman; Staffan Åkerblom; Dominique Bally; Nil Basu; Kevin Bishop; Nathalie Bodin; Hans Fredrik Veiteberg Braaten; Mark E. H. Burton; Paco Bustamante; Celia Chen; John Chételat; et al. (Ecotoxicology, 2024)
An important provision of the Minamata Convention on Mercury is to monitor and evaluate the effectiveness of the adopted measures and its implementation. Here, we describe for the first time currently available biotic mercury (Hg) data on a global scale to improve the understanding of global efforts to reduce the impact of Hg pollution on people and the environment. Data from the peer-reviewed literature were compiled in the Global Biotic Mercury Synthesis (GBMS) database (>550,000 data points). These data provide a foundation for establishing a biomonitoring framework needed to track Hg concentrations in biota globally. We describe Hg exposure in the taxa identified by the Minamata Convention: fish, sea turtles, birds, and marine mammals. Based on the GBMS database, Hg concentrations are presented at relevant geographic scales for continents and oceanic basins. We identify some effective regional templates for monitoring methylmercury (MeHg) availability in the environment, but overall illustrate that there is a general lack of regional biomonitoring initiatives around the world, especially in Africa, Australia, Indo-Pacific, Middle East, and South Atlantic and Pacific Oceans. Temporal trend data for Hg in biota are generally limited. Ecologically sensitive sites (where biota have above average MeHg tissue concentrations) have been identified throughout the world. Efforts to model and quantify ecosystem sensitivity locally, regionally, and globally could help establish effective and efficient biomonitoring programs. We present a framework for a global Hg biomonitoring network that includes a three-step continental and oceanic approach to integrate existing biomonitoring efforts and prioritize filling regional data gaps linked with key Hg sources. We describe a standardized approach that builds on an evidence-based evaluation to assess the Minamata Convention’s progress to reduce the impact of global Hg pollution on people and the environment.

Divergence in rates of phenotypic plasticity among ectotherms - Sigurd Einum; Tim Burton (Ecology Letters, 2023)
An individual's fitness cost associated with environmental change likely depends on the rate of adaptive phenotypic plasticity, and yet our understanding of plasticity rates in an ecological and evolutionary context remains limited. We provide the first quantitative synthesis of existing plasticity rate data, focusing on acclimation of temperature tolerance in ectothermic animals, where we demonstrate applicability of a recently proposed analytical approach. The analyses reveal considerable variation in plasticity rates of this trait among species, with half‐times (how long it takes for the initial deviation from the acclimated phenotype to be reduced by 50% when individuals are shifted to a new environment) ranging from 3.7 to 770.2 h. Furthermore, rates differ among higher taxa, being higher for amphibians and reptiles than for crustaceans and fishes, and with insects being intermediate. We argue that a more comprehensive understanding of phenotypic plasticity will be attained through increased focus on the rate parameter.

Environmental change and the rate of phenotypic plasticity - Tim Burton; Irja Ida Ratikainen; Sigurd Einum (Global Change Biology, 2022)
With rapid and less predictable environmental change emerging as the ‘new norm’, understanding how individuals tolerate environmental stress via plastic, often reversible changes to the phenotype (i.e., reversible phenotypic plasticity, RPP), remains a key issue in ecology. Here, we examine the potential for better understanding how organisms overcome environmental challenges within their own lifetimes by scrutinizing a somewhat overlooked aspect of RPP, namely the rate at which it can occur. Although recent advances in the field provide indication of the aspects of environmental change where RPP rates may be of particular ecological relevance, we observe that current theoretical models do not consider the evolutionary potential of the rate of RPP. Whilst recent theory underscores the importance of environmental predictability in determining the slope of the evolved reaction norm for a given trait (i.e., how much plasticity can occur), a hitherto neglected possibility is that the rate of plasticity might be a more dynamic component of this relationship than previously assumed. If the rate of plasticity itself can evolve, as empirical evidence foreshadows, rates of plasticity may have the potential to alter the level predictability in the environment as perceived by the organism and thus influence the slope of the evolved reaction norm. However, optimality in the rate of phenotypic plasticity, its evolutionary dynamics in different environments and influence of constraints imposed by associated costs remain unexplored and may represent fruitful avenues of exploration in future theoretical and empirical treatments of the topic. We conclude by reviewing published studies of RPP rates, providing suggestions for improving the measurement of RPP rates, both in terms of experimental design and in the statistical quantification of this component of plasticity.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Hierarchical analysis of wild Atlantic salmon ( Salmo salar ) fecundity in relation to body size and developmental traits - Nora Hanson; James Ounsley; Tim Burton; Sonya Auer; James H. Hunt; Brian Shaw; Jim Henderson; Stuart J. Middlemas (Journal of Fish Biology, 2020)
Using data from wild Atlantic salmon Salmo salar returning to spawn in seven Scottish rivers, we developed a model of fecundity based on individual body size and key developmental traits. We used a novel approach to model selection which maximises predictive accuracy for application to target river stocks to select the best from a suite of Bayesian hierarchical models. This approach aims to ensure the optimal model within the candidate set includes covariates that best predict out‐of‐sample data to estimate fecundity in areas where no direct observations are available. In addition to body size, the final model included the developmental characteristics of age at smolting and years spent at sea. Using two independent long‐term monitoring datasets, the consequences of ignoring these characteristics was revealed by comparing predictions from the best model with models that omitted them.

How to quantify thermal acclimation capacity? - Sigurd Einum; Irja Ratikainen; Jonathan Wright; Christophe Pélabon; Claus Bech; Fredrik Jutfelt; Clare Stawski; Tim Burton (Global Change Biology, 2019)

Early maternal experience shapes offspring performance in the wild - Tim Burton; S. McKelvey; D. C. Stewart; J. D. Armstrong; N. B. Metcalfe (Ecology, 2013)
Both the environments experienced by a mother as a juvenile and an adult can affect her investment in offspring. However, the implications of these maternal legacies, both juvenile and adult, for offspring fitness in natural populations are unclear. We investigated whether the juvenile growth rate and adult reproductive traits (length, body condition, and reproductive investment at spawning) of female wild Atlantic salmon ( Salmo salar ) were related to the growth and survival of their offspring. Adult salmon captured on their upstream migration were used to create experimental full‐sib clutches of eggs, which were mixed and then placed in artificial nests in a natural stream that lacked salmon due to a migration barrier. Four months later we resampled the stream to obtain family‐level estimates of offspring size and survival. Mothers that had grown slowly as juveniles (as determined by scalimetry) but had invested heavily in reproduction (egg production for a given body length) and were in relatively poor body condition (somatic mass for a given body length) at spawning produced the largest eggs. Larger eggs resulted in larger juveniles and higher juvenile survival. However, after controlling for egg size, offspring growth was positively related to maternal juvenile growth rate and reproductive investment. The predictors of offspring survival (i.e., reproductive success) varied with the juvenile growth rate of the mother: If females grew slowly as juveniles, their reproductive success was negatively related to their own body condition. In contrast, the reproductive success of females that grew quickly as juveniles was instead related positively to their own body condition. Our results show that maternal influences on offspring in the wild can be complex, with reproductive success related to the early life performance of the mother, as well as her state at the time of breeding.